The Effect of Training and Career Development on the Improvement of Police Personnel Performance at the Central Sulawesi Regional Police - Salmia Tri Agustina; Hasanuddin, Bakri; Kornelius, Yoberth; Ega Nugraha, Mohammad (Universitas Muhammadiyah Pontianak, 2026)
This study examines the impact of training and career development on the performance of police personnel at the Central Sulawesi Regional Police. The objective is to analyze both partial and simultaneous effects of these variables. A quantitative associative approach was employed with 384 respondents selected using stratified random sampling. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The results show that training and career development have positive and significant effects on performance, both individually and simultaneously, with an explanatory power of 79.5%. These findings imply the importance of improving training quality and implementing transparent, performance-based career development systems. Keywords: Training; Career Development; Performance; Police Personnel; Central Sulawesi Regional Police